2011
DOI: 10.1007/s12665-011-1205-7
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical attenuation for metallic remediation in a passive system for mine water treatment

Abstract: Passive systems with constructed wetlands have been consistently used to treat mine water from abandoned mines. Long-term and cost-effective remediation is a crucial expectation for these water treatment facilities. To achieve that, a complex chain of physical, chemical, biological, and mineralogical mechanisms for pollutants removal must be designed to simulate natural attenuation processes. This paper aims to present geochemical and mineralogical data obtained in a recently constructed passive system (from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…The higher REE contents found in the fine fractions of the Peliteira creek sediment after the discharge of the treated effluent and also after winter agrees with the lower contents found in the creek water. The fluffy ochre-precipitates formed in the limestone channel, which enters in the wetlands, certainly play an important role not only in metals/metalloids behavior like As, Zn and Mn as previously shown by Valente et al (2012), but also in REE, particularly the light ones, in a high water dynamics as shown in the present work. These studies revealed the broader applicability to the passive treatment systems of AMD, specifically for the removal and concentration of metals and metalloids, some potentially harmful, in ochre-precipitates and also in wetlands soils.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The higher REE contents found in the fine fractions of the Peliteira creek sediment after the discharge of the treated effluent and also after winter agrees with the lower contents found in the creek water. The fluffy ochre-precipitates formed in the limestone channel, which enters in the wetlands, certainly play an important role not only in metals/metalloids behavior like As, Zn and Mn as previously shown by Valente et al (2012), but also in REE, particularly the light ones, in a high water dynamics as shown in the present work. These studies revealed the broader applicability to the passive treatment systems of AMD, specifically for the removal and concentration of metals and metalloids, some potentially harmful, in ochre-precipitates and also in wetlands soils.…”
Section: Discussionsupporting
confidence: 78%
“…Comparing the REE results in the fine fractions, particularly the <20 lm fraction, of the wetland soils with chemical and mineralogical results previously obtained by Valente et al (2012), a positive correlation between REE and manganese appears to exist. Also among phylossilicates, clay minerals with low degree of order such as mica-vermiculite mixed-layer and kaolinite may play a relevant role adsorbing REE in the wetlands.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In addition to the minerals identified by XRD, amorphous precipitates made of iron and sulphate are expected to form under these conditions, in agreement with results obtained by Valente et al (2012b). Further research on this reservoir should be focused on nanoprecipitates (defined as b100 nm in size).…”
Section: Mineralogical Hostssupporting
confidence: 84%